Athlete perspectives on the enablers and barriers to nutritional adherence in high-performance sport. (January 2021) - Bentley, Meghan R.N.; Patterson, Laurie B.; Mitchell, Nigel; Backhouse, Susan H.
Abstract: Objectives: Poor adherence to nutritional guidance by athletes may compromise their health and performance. Enhancing adherence is therefore an important performance and welfare strategy. The aim of this study was to qualitatively explore the barriers and enablers of elite athletes' adherence to nutritional guidelines. Design: Underpinned by our constructionist epistemological position and our relativist ontology, we conducted a qualitative study using focus groups. Methods: We used the Capability, Opportunity, and Motivation Behaviour (COM-B) model and the Theoretical Domains Framework (TDF) to conduct focus group discussions with a purposive sample of 39 UK-based funded athletes (mean age = 23 ± 3.81), participating in either Olympic and Paralympic sport (n = 30) or professional sport (n = 9), who had access to a nutritionist. Data were analysed using reflexive thematic analysis. Results: Athlete adherence to nutritional guidance was seasonal and included inadequate energy intakes and episodes of binge eating. Underpinning these behaviours, athletes' emotional barriers (motivation) are reinforced through their social interactions within the high-performance environment (opportunity) and athletes' training environment limits developmental opportunities for food planning (capability). However, a holistic-developmental approach by the sports nutritionists (opportunity) supports athlete wellbeing and nutritional adherence. Conclusion: These findings advance theoretical understanding of the barriers and enablers of nutritional adherence amongst elite-level athletes in high-performance sport and present a number of significant implications for athlete support personnel seeking to enhance performance in demanding sporting contexts. Drawing on the Behaviour Change Wheel (BCW), recommendations include the need to 1) train and educate sports nutritionists in human behaviour, 2) update regulations for sports nutrition profession practice to acknowledge the skills required to support athletes' emotional wellbeing, 3), educate coaches on the sensitivity of body weight and composition and develop guidelines for monitoring athletes' body weight and composition in sport, 4) persuade influential leaders to develop culture guidelines that shift the performance-narrative of high-performance (i.e., environmental restructuring ). Highlights: Poor nutritional adherence may compromise athlete health and performance. A behavioural analysis of nutritional adherence in sport has not been published. A complex combination of factors influence athletes' dietary behaviour. Emotions are pertinent, emanating from the person and reinforced by the environment. Multifaceted programmes, addressing the individual and environment, are needed.